A utilização da internet por organizações não-governamentais que promovam o desenvolvimento rural - Silva, Cristiane Camargo da (2006)
The present study was carried out in two non-government organizations, CAPA - Center of Support to the small farm worker- and MST - movement of the landless farm workers, from October 2005 to February 2006, aiming to analyze the use of the internet by these organizations in order to promote the rural development. The methodology employed was a combination of quantitative and qualitative techniques called “Q methodology”. Its use implies three stages: i) qualified informants were used to build the statements to be tested for the directed sample; ii) these statements were administered to 32 members of these social movements for them to classify; iii) the results were analyzed using a statistical program called PCQ (factorial analysis). The results led to the existence of four factors (groups of people), where all of them perceived the importance of the internet for the rural development. The factor A (internet & the organizations) believes that the collective appropriation, through entities, can be a better way to take advantage of Internet than a single farm worker’s appropriation. The factor B ( the internet & subjects) is worried about the appropriation by the small farm worker. The factor C ( the internet – politics) it is concerned about the people's possibilities to use Internet, since there are not enough public resources to facilitate access to internet in the countryside. The factor D ( the internet & broadcasting strategies) is concerned about the strategies to broadcast the movement. By analyzing all these factors, it is observed that all agree in internet as a great possibility of development for the farm workers and rural organizations, like MST, because permits to obtain information and also to interact among the people involved (generating empowerment). The present study concluded that nowadays the social organizations that promote rural development should use this democratic network called 'internet'.